Childhood emotional abuse and adult mental health at the intersection of social relationship and education - Jung, Jong Hyun (2023)
Background: Previous research has established that childhood emotional abuse has long-term, negative consequences for adult mental health. Yet, less is known about the ways that social relationship and education intersect to shape the link between childhood emotional abuse and mental health in adulthood. Aim: The current study aims to examine whether perceived quality of social relationships moderates the association between childhood emotional abuse and adult mental health. Moreover, it assesses how the moderating effect of perceived quality of social relationship differs across levels of education. Method: The current study analyzes data from the 2012 Korean General Social Survey, a nationally representative sampling of Korean adults. It uses OLS regression models. Results: Childhood emotional abuse is positively associated with depression and psychological distress in adulthood. However, perceived quality of social relationships mitigates the positive association of childhood emotional abuse with depression and psychological distress. Further, this buffering effect of perceived quality of social relationships operates only for individuals with less than or equal to a high school education, but not for individuals with college education or more. Conclusion: The results lend support to the resource substitution thesis, suggesting that positive perceptions of social relationship act as a protective factor against childhood emotional abuse for individuals with lower levels of education.